2006
DOI: 10.1179/174329306x94291
|View full text |Cite
|
Sign up to set email alerts
|

Microcracking in multipass weld metal of alloy 690 Part 1 – Microcracking susceptibility in reheated weld metal

Abstract: Microcracking behaviour in the gas tungsten arc multipass weld metal of alloy 690 was investigated. The majority of microcracks occurred within about 300 mm from the fusion line of the subsequent weld bead and propagated along the solidification boundaries in the multipass weld metal. The morphology of the crack surface indicated the characteristic texture of ductility dip cracking. The microcracking susceptibility of the reheated weld metal was evaluated via the spot Varestraint test using three different fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Based on the above result, it can be concluded that the next-pass welding has most contribution to DDC in weld joint. The result turns out to be very similar to Nishimoto's study [6]. In his work, the multi-pass weld joint has Ductility Dip Cracks in every pass weld, except the last one.…”
Section: Ddc Susceptibility Under Complex Stress Statesupporting
confidence: 84%
“…Based on the above result, it can be concluded that the next-pass welding has most contribution to DDC in weld joint. The result turns out to be very similar to Nishimoto's study [6]. In his work, the multi-pass weld joint has Ductility Dip Cracks in every pass weld, except the last one.…”
Section: Ddc Susceptibility Under Complex Stress Statesupporting
confidence: 84%
“…It is also used in dissimilar welding between several Ni-base alloy, stainless steel and carbon steel in building nuclear power plants [9] . However, it has been pointed out that NiCrFe-7 weld metal is susceptible to ductility-dip-cracking (DDC) under heavy restraint conditions such as welding thick components [10][11][12][13] . DDC is a solid-state hot cracking, caused by GB embrittlement at homologous temperatures that ranges from about 0.5 to 0.8 of the alloy melting points, which is observed at grain boundaries (GBs) [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Filler metal composition, such as S, P, H, C, Ti, Ta, Mo, La, Ce, and Nb, has a strong effect on DDC formation in austenitic weldments. Segregation of S, P, and H to GBs is a dominant factor for DDC aggravation in Ni-base alloys, whereas Ti, Ta, Mo, La, Ce, and Nb addition to a filler metal reduces the sensitivity of DDC [13,17,20,[27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…The welded joints of Inconel 690 with appropriate filler materials showed a high sensitivity to hot crack formation, particularly under the conditions of welding of thick-walled structural elements. The alloys manifest the highest tendency to the formation of ductility-dip cracks [2,3].As was shown previously [4], the ductility-dip cracks in welding of alloys of alloying system Ni-Cr-Fe occur at the temperature range of 1050-650 °C, the value of critical deformation of crack formation ε cr is about 1.2 %.The thermal processes in fusion welding have a decisive influence on the nature and kinetics of changes in the stress-strain state, structure and properties of weld and HAZ. In this regard, the analysis of temperature fields in welding of alloys of Ni-Cr-Fe alloying system with the aim of further investigations of kinetics of stress-strain state and evaluation of tendency to hot crack formation is an urgent problem.…”
mentioning
confidence: 99%
“…The welded joints of Inconel 690 with appropriate filler materials showed a high sensitivity to hot crack formation, particularly under the conditions of welding of thick-walled structural elements. The alloys manifest the highest tendency to the formation of ductility-dip cracks [2,3].…”
mentioning
confidence: 99%